2009
DOI: 10.1080/03004270802095421
|View full text |Cite
|
Sign up to set email alerts
|

Children's views of collaborative learning

Abstract: Collaborative learning is a widely used and popular strategy in many primary schools. In this article, the authors review the nature and purpose of collaborative learning and present a summary of how one small group of Year 5/6 children view its effectiveness. IntroductionCollaborative learning is a widely used strategy in primary schools and its popularity is reflected in classroom seating arrangements and the regular use of group and paired work. Collaborative learning occurs when children work together to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
3
Order By: Relevance
“…As pointed out by different authors, collaborative learning oriented to younger students can encourage intellectual progress (Azmitia, 2000;Clark et al, 2003;Howe & Tolmie, 1998). It also helps children to develop their knowledge, language, social skills, comprehension of new ideas, and planning to achieve a common goal or to solve a problem (Tunnard & Sharp, 2009). Considering some difficulties encountered by teachers when applying the lesson plans, it is necessary to adjust the timing proposed for certain activities and to some materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by different authors, collaborative learning oriented to younger students can encourage intellectual progress (Azmitia, 2000;Clark et al, 2003;Howe & Tolmie, 1998). It also helps children to develop their knowledge, language, social skills, comprehension of new ideas, and planning to achieve a common goal or to solve a problem (Tunnard & Sharp, 2009). Considering some difficulties encountered by teachers when applying the lesson plans, it is necessary to adjust the timing proposed for certain activities and to some materials.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tunnard and Sharp (2009), collaborative learning occurs when children work together to achieve a common goal or to solve a problem. The authors reported that many quantitative studies of learning behaviors and outcomes have indicated that collaboration between peers can help children to develop their knowledge, language, and social skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beauchamp, 2011;Davidsen & Vanderlinde, 2016). Vähemmän on kuitenkin tutkittu yhteisöllistä oppimista perusasteen oppilaiden itsensä kuvailemana (Tunnard & Sharp, 2009). Samoin STEAM-kontekstissa tapahtuvaa yhteisöllistä oppimista on toistaiseksi tutkittu vähän, erityisesti suomalaisen koulun viitekehyksessä.…”
Section: Johdantounclassified
“…Myös aiemmat tutkimukset ovat osoittaneet oppijoiden suhtautuvan STEAM-projekteihin positiivisesti (esim. Julià & Antoli, 2019;Ozkan & Topsakal, 2017;Tunnard & Sharp, 2009).…”
Section: Pohdinta Ja Johtopäätöksetunclassified
See 1 more Smart Citation